Synthesis and structural studies of S-type/N-type-locked/frozen nucleoside analogues and their incorporation in RNA-selective, nuclease resistant 2 `-5 ` linked oligonucleotides - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Gonnade, Rajesh G.; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2013)
2'-endo locked or frozen (S-type)/3'-endo locked or frozen (N-type) nucleoside analogues were synthesized. Conformational analysis based on (3)J(HH) and NOE measurements is presented which is further confirmed by X-ray crystal structural studies. 2'-5' isoDNA oligonucleotides (ON) were synthesized using these modified nucleoside analogues and UV-T-m studies of the resultant 2'-5' isoDNA : RNA duplexes reflect the site-and sequence-dependent effects and confirm that the S-type sugar conformations were preferred over the N-type sugar geometry in such duplexes.

Second generation, arginine-rich (R-X `-R)(4)-type cell-penetrating alpha-omega-alpha-peptides with constrained, chiral omega-amino acids (X `) for enhanced cargo delivery into cells - Patil, Kiran M.; Naik, Rangeetha J.; Vij, Manika; Yadav, Amit K.; Kumar, Vaijayanti A.; Ganguli, Munia; Fernandes, Moneesha (Bioorganic & Medicinal Chemistry Letters, 2014)
The syntheses of novel N-aminoalkyl proline-derived spacers (X') in polycationic (R-X'-R)-motif cell-penetrating alpha-omega-alpha-peptides are described as improved molecular transporters and their structural features studied by CD. FACS analysis shows enhanced cellular uptake and confocal microscopy indicates predominantly cytoplasmic localization. The oligomers are efficient at transporting pDNA into cells. The chirality together with the hydrophobicity and flexibility derived from the spacer chain are found to have marked influence on the cell-penetrating and cargo delivery properties of the cell-penetrating peptides (CPPs). The peptides containing N-(3-aminopropyl)-D-proline spacers are found to be the best at cell penetration and cargo delivery in the present study. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R-X-R)-motif; alpha-omega-alpha-Peptide; Cell-penetrating peptide; Constrained chiral amino acid; Peptidomimetics

Superior HIV-1 TAR binders with conformationally constrained R52 arginine mimics in the Tat(48-57) peptide - Bhosle, Govind S.; Kharche, Shalmali; Kumar, Santosh; Sengupta, Durba; Maiti, Souvik; Fernandes, Moneesha (Chemmedchem, 2018)
We report a 100-fold increase in binding affinity of the Tat(48-57) peptide to HIV-1 transcriptional activator-responsive element (TAR) RNA by replacing Arg52, an essential and critical residue for Tat's specific binding, with (2S,4S)-4-guanidinoproline. The resulting Tat1M peptide is a far superior binder than Tat1M, a peptide containing another conformationally constrained arginine mimic, (2S,4S)-4-amino-N-(3-guanidinopropyl)proline, or even the control Tat peptide (CtrlTat) itself. Our observations are supported by circular dichroism (CD), isothermal titration calorimetry (ITC), gel electrophoresis and UV spectroscopy studies. Molecular dynamics simulations suggest increased interactions between the more compact Tat1M and TAR RNA, relative to CtrlTat. The CD signature of the RNA itself remains largely unchanged upon binding of the peptides. The Tat mimetics further have better cell uptake properties than the control Tat peptide, thus increasing their potential application as specific TAR-binding molecules.
Keywords: antiviral agents; arginine mimics; RNA; Tat peptide analogues; Tat-TAR binding